The Impacts of Disaster Risk on Sovereign Asset and Liability Management - World Bank (World Bank, Washington, DC, 2021)
Implicit contingent liabilities, such as those generated by natural disasters, are often not quantified in the government balance sheet. However, when they materialize, they place pressure on government finances that may raise interest expenditures and financial risks. Understanding the impacts of disaster risk on sovereign assets and liabilities plays a key part in understanding the potential impact of sovereign disaster risk finance strategies which allow governments to reduce the costs and risks of disasters using prearranged financing and insurance methods. Applying the Sovereign Asset and Liability Management (SALM) framework is a new and comprehensive way of looking at the potential impact of a disaster on the public sector balance sheet through assets and liabilities. This paper introduces a framework that identifies three channels through which natural disaster will impact SALM. This framework is applied in three case studies, Peru, Serbia and New Zealand to derive lessons about the potential impact of natural disasters on the sovereign balance sheet and highlight the importance of accounting for disaster impacts across public sector balance sheets. The application of SALM can increase countries’ resilience to financial shocks posed by disaster risk through improved understanding of the impacts of disaster risk on both sides of the sovereign balance sheet. Going forward it could even be used to define a country’s risk tolerance to disaster risk, monitor changes in this position and help to inform policy design on disaster risk and where needed support the introduction of financial instruments to manage disaster risk.